2021
DOI: 10.1007/s00455-021-10362-9
|View full text |Cite
|
Sign up to set email alerts
|

Finnish Version of the Eating Assessment Tool (F-EAT-10): A Valid and Reliable Patient-reported Outcome Measure for Dysphagia Evaluation

Abstract: Our aim was to validate a Finnish version of the Eating Assessment Tool (F-EAT-10) for clinical use and to test its reliability and validity in a multicenter nationwide study. Normative data were acquired from 180 non-dysphagic participants (median age 57.0 years, 62.2% female). Dysphagia patients (n = 117, median age 69.7 years, 53.0% female) referred to fiberoptic endoscopic evaluation of swallowing (FEES) completed F-EAT-10 before the examination and after 2 weeks. Patients underwent the 100-ml water swallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…This study demonstrated a very high internal consistency of the Slovak EAT10 ® . Similar results have been reported by foreign adaptations of EAT10 ® ; Cronbach’s α ranged from 0.87 [ 27 ] to 0.963 [ 22 , 28 , 29 ]. The same Cronbach’s α as for the Slovak version of EAT10 ® was calculated for the German adaptation of EAT10 ® [ 30 ].…”
Section: Discussionsupporting
confidence: 86%
“…This study demonstrated a very high internal consistency of the Slovak EAT10 ® . Similar results have been reported by foreign adaptations of EAT10 ® ; Cronbach’s α ranged from 0.87 [ 27 ] to 0.963 [ 22 , 28 , 29 ]. The same Cronbach’s α as for the Slovak version of EAT10 ® was calculated for the German adaptation of EAT10 ® [ 30 ].…”
Section: Discussionsupporting
confidence: 86%
“…The meta-analysis included 1064 subjects from 7 countries, including healthy people and people at high risk for dysphagia, such as those with PD [ 52 ], stroke [ 34 ], amyotrophic lateral sclerosis (ALS) [ 53 ], aging [ 49 ], neurodegenerative diseases [ 36 , 49 ], demyelinating disease [ 44 ], and gastroesophageal reflux disease [ 44 ]. Four studies [ 34 , 44 , 49 , 53 ] used VFSS and three studies [ 36 , 47 , 52 ] used FEES as the gold standard for reporting the sensitivity and specificity of EAT-10. Cross-sectional studies [ 34 , 36 , 44 , 52 , 53 ] and case–control studies [ 47 , 49 ] were included.…”
Section: Resultsmentioning
confidence: 99%
“…Acknowledgements Diagnostic accuracy of the Eating Assessment Tool-10 (EAT-10) in screening dysphagia: a meta-analysis registered in the International Prospective Register of Systematic Reviews (PROS-PERO), number CRD42020164655. [47] 2016 Abu-Ghanem 0.96 0.98 Spanish [48] 2016 Giraldo-Cadavid 0.91 0.94 Swedish [40] 2016 Möller 0.88 0.90 Turkish [49] 2016 Demir 0.90 0.91 a Pediatric [50] 2018 Serel Arslan 0.87 NM Greek [45] 2018 Printza 0.96 NM Hebrew [44] 2019 Shapira-Galitz 0.93 0.82 a French [46] 2019 Lechien 0.95 0.92 a Finland [51] 2021 Järvenpää 0.84 0.93…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations